2019
DOI: 10.3390/cells8050497
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate Filaments as Effectors of Cancer Development and Metastasis: A Focus on Keratins, Vimentin, and Nestin

Abstract: Intermediate filament (IF) proteins make up the largest family of cytoskeletal proteins in metazoans, and are traditionally known for their roles in fostering structural integrity in cells and tissues. Remarkably, individual IF genes are tightly regulated in a fashion that reflects the type of tissue, its developmental and differentiation stages, and biological context. In cancer, IF proteins serve as diagnostic markers, as tumor cells partially retain their original signature expression of IF proteins. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(104 citation statements)
references
References 161 publications
(237 reference statements)
2
99
1
1
Order By: Relevance
“…Reports about the effect of keratins on the migratory phenotype differ vastly (selected examples in Table 2; [4,17,111]). Although the listed and other obvious discrepancies may be explained by technical flaws, use of different assay systems and the analysis of different parameters, they are so numerous that they likely point to context-dependent effects Mechanical cues provided by the environment act primarily on FAs and adherens junctions, both of which activate the acto-myosin system as the major force-generating machinery.…”
Section: Discussionmentioning
confidence: 99%
“…Reports about the effect of keratins on the migratory phenotype differ vastly (selected examples in Table 2; [4,17,111]). Although the listed and other obvious discrepancies may be explained by technical flaws, use of different assay systems and the analysis of different parameters, they are so numerous that they likely point to context-dependent effects Mechanical cues provided by the environment act primarily on FAs and adherens junctions, both of which activate the acto-myosin system as the major force-generating machinery.…”
Section: Discussionmentioning
confidence: 99%
“…The eukaryotic translation elongation factor EEF1A1 which is overexpressed in the majority of breast cancers and protects tumor cells from proteotoxic stress (Lin et al, 2018) was the sole factor that was selected in all of the 97 test set patients. Other frequently selected features in both non-metastatic as well as metastatic patients included genes such as the Epithelial-to-Mesenchymal-Transition (EMT)related gene VIM (46/58 non-metastatic, 30/39 metastatic patients), the extracellular matrix protein FN1 (43/58 non-metastatic, 22/39 metastatic patients), the actin cytoskeleton regulator CFL1 (7/58 non-metastatic, 7/39 metastatic patients) as well as the estrogen receptor ESR1 28/58 non-metastatic, 10/39 metastatic patients) that are all known to be linked with breast cancer development and progression (Sharma et al, 2019;Wang, Eddy, and Condeelis, 2007;Lin et al, 2019;Feng et al, 2018) This indicates that our method successfully identified relevant key players with a general role in breast tumorigenesis.…”
Section: Glrp To Deliver Patient-specific Subnetworkmentioning
confidence: 99%
“…These might be toxic and lead to the dominant phenotypes of these disease‐associated alleles. Abnormal accumulation of IF proteins has also been noted in multiple degenerative diseases (Alzheimer's, Parkinson's, Huntington's, spastic paraplegia, spinal muscular atrophy, giant axonal neuropathy), neuropsychiatric disorders (drug addiction, schizophrenia, bipolar disorder), and others (cancer, diabetic neuropathy, traumatic brain injury) (Didonna & Opal, ; Eriksson et al, ; Godsel, Hobbs, & Green, ; Mahammad et al, ; Omary, ; Omary, Coulombe, & Mclean, ; Perrot, Berges, Bocquet, & Eyer, ; Perrot & Eyer, ; Sharma, Alsharif, Fallatah, & Chung, ; Yuan & Nixon, ). These diseases and disorders can often occur even in the apparent absence of mutations in the neuronal IF genes (Barry et al, ).…”
Section: An Introduction To Intermediate Filamentsmentioning
confidence: 99%